2010
DOI: 10.1080/15287394.2010.514225
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Susceptibility to Benzo[a]Pyrene: Tissue Burden of Metabolites and DNA Adducts in F-344 Rats

Abstract: Exposure to environmental toxicants has been implicated as one of the causative factors for infertility in mammals. The objective of this study was to determine the amount of ingested benzo[a]pyrene (BaP), an environmental toxicant that reaches the reproductive tissues (internal dose) subsequent to a single acute exposure. Toward this end, the concentrations of BaP reactive metabolites and BaP-DNA adducts were measured throughout the course of BaP's residence in the body. Ten-week-old female Fischer-344 rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…57 This method is effective and economical, but is limited to hydrophobic lesions such as those of polycyclic aromatic hydrocarbons and aromatic amines.…”
Section: Introductionmentioning
confidence: 99%
“…57 This method is effective and economical, but is limited to hydrophobic lesions such as those of polycyclic aromatic hydrocarbons and aromatic amines.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear how these translate for the woman that smokes cigarettes while attempting to conceive; however, it is known that smoking leads to a reduction in ovarian reserve and an advancement of the age of menopause for the woman (167,301), potentially due to the influence of polycyclic hydrocarbons which are activated into more toxic metabolites by the liver (49,271). Further human studies have demonstrated that oocytes derived from cigarette smoking women undergoing IVF treatment have a greater number of immature oocytes (385), an increased thickness of the zona pellucida (310), with follicles containing higher level of markers of oxidative stress within the follicular fluid (252), and within the cumulus (316).…”
Section: Ovarian Functionmentioning
confidence: 99%
“…Additionally, the preponderance of BaP-7,8-dihydro-diol in these samples is interesting, given the fact that this precursor of BPDE has been linked to BaP-induced cancer 38 and infertility. 13 …”
Section: Discussionmentioning
confidence: 99%
“…BaP metabolites were extracted twice with ethyl acetate and the extracts were analyzed by reverse phase HPLC for BaP metabolites as described previously. 13 Metabolite standards were obtained from the National Cancer Institute Chemical Carcinogen Repository (Midwest Research Institute, Kansas City, Missouri, USA).…”
Section: Methodsmentioning
confidence: 99%